Vertebral osteomyelitis associated with Enterococcus faecalis in Broiler Breeders in Chile - Cádiz, Leandro; Guzmán, Miguel; Navarrete, Fernando; Torres, Paulina; Hidalgo, Héctor (Austral Journal of Veterinary Sciences, 2023)
Vertebral osteomyelitis is a re-emerging disease characterized by inflammation and necrosis of the thoracic vertebral body, caused by Enterococcus cecorum. Here, we report the first case of vertebral osteomyelitis caused by Enterococcus faecalis in Broiler Breeders, in Chile, which also causes infections in humans and is resistant to multiple antimicrobials, representing a risk to public health.